Draft Annual Plan 1976-77 Statements Fifth Five Year Plan Union Territory of Pondicherry - Planning Commission (Planning Commission, 1976)
Major Heads - Outlays and Expenditure Minor Heads - Outlays and Expenditure Development Programmes - Targets and Achievements Minimum Needs Programme - Outlays and Expenditure - Targets and Achievements Centrally Sponsored Schemes - Outlays and Expenditure.
Government of Pondicherry, Planning and Research Department